DEVELOPMENT ELDERLY QUALITY OF LIFE UNDER THE GOVERNMENT POLICY OF HUAHIN MUNICIPALITY, PRACHUAP KHIRI KHAN PROVINCE - Lekky, Boongua; Sartngern, Phachara (Journal of MCU Phetchaburi Review, 2025)
This mixed-methods research aimed to 1) study the quality of life of the elderly according to government policy; 2) study the differences between personal characteristics and quality of life of the elderly according to government policy; 3) study the causal relationship between factors in providing welfare for the elderly and quality of life of the elderly according to government policy; and 4) study the guidelines for improving the quality of life of the elderly according to government policy. The sample consisted of 400 elderly aged 60 years and over residing in Hua Hin Municipality and 8 key informants. Data were analyzed using percentages, means, standard deviations, t-tests, one-way ANOVA, multiple regression, and content analysis. The results revealed that 1) the quality of life of the elderly according to government policy is at a high level; 2) different personal characteristics did not differ from each other in terms of quality of life of the elderly according to government policy; and 3) factors in providing welfare for the elderly, including medical and public health services and welfare allowances, have a causal relationship with quality of life of the elderly according to government policy with a statistically significant level of 0.001. Social activities and public facilities and services have a causal relationship with quality of life of the elderly according to government policy. Statistically significant at the 0.01 level and 4) guidelines for improving the quality of life of the elderly according to government policy found that additional occupations should be provided for the elderly, there should be a security guard to monitor safety within the community, there should be regular health checks for the elderly, the environment within the community should be created to be safe, there should be a club for the elderly, activities should be organized to build relationships between the elderly, people in the community and children.